2013
DOI: 10.3174/ajnr.a3484
|View full text |Cite
|
Sign up to set email alerts
|

3D Cine Phase-Contrast MRI at 3T in Intracranial Aneurysms Compared with Patient-Specific Computational Fluid Dynamics

Abstract: BACKGROUND AND PURPOSE: CFD has been proved valuable for simulating blood flow in intracranial aneurysms, which may add to better rupture risk assessment. However, CFD has drawbacks such as the sensitivity to assumptions needed for the model, which may hinder its clinical implementation. 3D PC-MR imaging is a technique that enables measurements of blood flow. The purpose of this study was to compare flow patterns on the basis of 3D PC-MR imaging with CFD estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…4D flow MR imaging may yield poor-quality images due to motion artifacts attributable to a relatively long acquisition time 21 and limited spatial resolution. [9][10][11][12][13][14]17,20,22,[25][26][27] Because flow quantification by using 4D flow MR imaging requires at least 16 isotropic voxels over the vessel lumen area, 31 a spatial resolution of 1.0 mm in the isotropic voxel dimensions is needed to evaluate the flow conditions in aneurysms with a diameter of 4.0 mm. 22 Although only 1.5T MR imaging scanners are available at our institution, high-resolution MR imaging on greater than 3T instruments may make it possible to evaluate the inflow jets of aneurysms smaller than 4.0 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4D flow MR imaging may yield poor-quality images due to motion artifacts attributable to a relatively long acquisition time 21 and limited spatial resolution. [9][10][11][12][13][14]17,20,22,[25][26][27] Because flow quantification by using 4D flow MR imaging requires at least 16 isotropic voxels over the vessel lumen area, 31 a spatial resolution of 1.0 mm in the isotropic voxel dimensions is needed to evaluate the flow conditions in aneurysms with a diameter of 4.0 mm. 22 Although only 1.5T MR imaging scanners are available at our institution, high-resolution MR imaging on greater than 3T instruments may make it possible to evaluate the inflow jets of aneurysms smaller than 4.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] For the quantitative evaluation of the hemodynamics in real human cerebral aneurysms, 4D flow MR imaging, which is based on time-resolved 3D cine phase-contrast MR imaging techniques, has been used. [9][10][11][12][13][14][15][16][17][18][19][20] In this study, we investigated the visualization threshold on the basis of the flow velocity in the parent artery to classify the inflow jet patterns of unruptured cerebral aneurysms on 4D flow MR imaging. We applied different thresholds to visualize the inflow streamlines, evaluated the inflow jet patterns, and examined the relationship between the inflow jet pattern and the inflow hemodynamics.…”
mentioning
confidence: 99%
“…[37][38][39] Moreover, previous studies confirmed the feasibility of depicting the aneurysmal inflow. 18,20,23,26,27 Consequently, 4D flow MR imaging is the criterion standard for the identification of the inflow zone of cerebral aneurysms. According to others, 11,13,40 the inflow zone of lateral-projection aneurysms was located on the distal neck.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, 4D flow MR imaging based on time-resolved 3D cine phase-contrast MR imaging techniques was used to evaluate the hemodynamics of cerebral aneurysms. [18][19][20][21][22][23][24][25][26][27] However, 4D flow MR imaging requires additional time for data acquisition, and TC 3D MRA may be a convenient alternative to 4D flow MR imaging for identifying the aneurysmal inflow zone.…”
Section: -15mentioning
confidence: 99%
“…In-house-developed software was used to impose PC-MR imaging-measured spatiotemporal velocity profiles as inflow boundary conditions. 16 In case of anterior communicating artery aneurysms, DSA images were reviewed by 2 neuroradiologists to determine the afferent artery. None of the anterior communicating artery aneurysms filled from both A1s.…”
Section: Hemodynamic Modeling and Visualizationmentioning
confidence: 99%